126k views
0 votes
How do I do this?

-2(6-r)=4

2 Answers

3 votes

To solve this, you need to isolate/get the variable "r" by itself in the equation:

-2(6 - r) = 4 Divide -2 on both sides


(-2(6-r))/(-2) =(4)/(-2)

6 - r = -2 Subtract 6 on both sides

6 - 6 - r = -2 - 6

-r = -8 Divide -1 on both sides to get "r" by itself


(-r)/(-1)=(-8)/(-1) (two negative signs cancel each other out and become positive)

r = 8

PROOF

-2(6 - r) = 4 Substitute/plug in 8 into "r"

-2(6 - 8) = 4

-2(-2) = 4

4 = 4

User KarthiS
by
5.4k points
5 votes

Answer:r=8

Explanation:

User ShujatAli
by
5.5k points